TI_GERICHTE 52.2019.272 vom 9. Mai 2019 , Divieto d'uso delle serre per la coltivazione della canapa. Effetto sospensivo - TI Tribunale d'appello (2019)
Divieto d'uso delle serre per la coltivazione della canapa. Effetto sospensivo